Cytogenetics of three Brazilian Goniosoma species: A new record for diploid number in Laniatores (Opiliones, Gonyleptidae, Goniosomatinae) - Oliveira, Rosangela Martins; Zacaro, Adilson Ariza; Gnaspini, Pedro; Cella, Doralice Maria (Amer Arachnological Soc, 2006)
Currently, 60 species of harvestmen have been karyotyped and all of these are from the Nearctic and Palearctic regions. This work is the first cytogenetic report of three gonyleptid species of the suborder Laniatores: Goniosoina aff. badiuln, G. proxiinuni and G. spelaeum of the Neotropical region, from the southeastern region of Brazil. Conventional Giemsa stain chromosome preparations were obtained from embryonic cells and adult male testes. Embryo mitotic plates of G. aff. badium and G. proximum indicated 88 chromosomes, and mitotic spermatogonial plates of G. spelaeum males revealed intra- and interindividual variation of chromosome number, ranging from 92-109 chromosomes. In the three analyzed species, the mitotic chromosomes were meta- or subinetacentric with no obvious sex chromosomes being identified during mitosis. Prophase I spermatocytes of G. spelaeum also revealed intra- and interindividual bivalent number variation and furthermore indicated the presence of multivalence. The karyotypes of these three Goniosoina species exhibited the largest chromosome pair with a negative heteropycnosis in the distal region of the shortest arrn chromosomes of G. spelaeum submitted to silver impregnation evidenced this negative heteropycnotic region as nucleolus organizer region (NOR). These results, when compared with cytogenetic data of other Laniatores species from the Palearctic region, indicated that a new record for diploid chromosome number probably characterize the genus Goniosoma in the Neotropical region.
Keywords: chiasma; chromosome chain; karyotype; Palpatores; meiosis